Uma investigação sobre a relação entre Disclosure Ambiental e o setor econômico das empresas listadas na B3 no ano de 2017 - Santos, Fernanda Patrícia Bastos dos (2019)
This study aimed to investigate the economic sectors of the companies listed in B3 that most disseminated environmental information in the year of 2017. In this perspective, a descriptive research was carried out, regarding the objectives, with procedures of documentary collection and qualitative approach. The sample consisted of 150 companies and verified the Annual Sustainability Reports, the Management Reports and the Explanatory Notes of it for the year of 2017. The environmental information surveyed was classified into categories and subcategories according to the study of Murcia et al. (2008). The results show that the category with the highest number of sentences is "Impacts of Products and Processes" followed by "Environmental Policies". It was verified that the highlight sectors, according to the highest level of disclosure, were "Products of Personal Use and Cleaning", "Construction and Engineering", followed by "Transport Material", "Wood and Paper" and "Chemicals". In addition to that, it was observed that the companies that most disseminated environmental information in the year of 2017 belong to the "Transportation" sector, followed by the "Wood and Paper" sector. With this, it is possible to notice that companies that practice potentially polluting activities tend to disclose higher levels of environmental information, thus being more transparent about their actions towards the environment.